(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2016)
Science-Technology-Society (STS) is an approach that recognizes science and technology as complex social processes and that is established at the confluence of several search fields. This article aims to identify which research themes are related to STS in the Brazilian academic production. Therefore, as a methodological tool, we opted for using the Network Analysis on the keywords of 144 articles published in journals of the field. When viewing the network, the generated image resembled an orbital, showing STS in the center and the other 173 keywords around it. Based on the network centrality measures, we identify the twenty most relevant keywords, which composed a set of research themes connected to STS. The qualitative analysis of this set generated a review of the Brazilian production in STS Education.